Analisis Kompetensi Andragogi Tutor Pendidikan Kesetaraan dalam Pembelajaran di Sanggar Kegiatan Belajar (SKB) Kota Medan - Nst, Sofwatun Nabilah; Anifah, Anifah (IAI Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the competence of equal education tutors in the Medan City Community Learning Activity Studio (SKB). The type of research used is qualitative descriptive research. There were 3 subjects in the research, namely tutors in the equivalency program. The data collection techniques used were observation, interviews and documentation. Data analysis techniques are data reduction, data presentation and drawing conclusions. The validity of the research includes source triangulation and technique triangulation. The research results show that tutors have shown significant efforts in understanding the characteristics and needs of students by approaching them directly and identifying individual habits and needs. Mastery of educational principles can also be seen through the tutor's efforts to integrate educational principles in learning by creating an active and interesting class atmosphere. In terms of curriculum development, tutors collaborate with external parties to ensure the relevance and effectiveness of the curriculum according to student needs, by paying attention to basic principles such as relevance and efficiency. The learning strategies implemented, including discussion methods and the use of simple language, succeeded in increasing students' understanding. Apart from that, tutors are able to create interactive, fun and challenging learning situations. Mastery of conventional learning media is good, but use of information and communication technology (ICT) varies, with some tutors facing technical and infrastructure obstacles. Finally, assessments are carried out using various tools, both tests and non-tests, to ensure fair and objective learning outcomes.